Competing Endogenous RNA (ceRNA) Networks and Splicing Switches in Cervical Cancer: HPV Oncogenesis, Clinical Significance and Therapeutic Opportunities - Afra Basera; Rodney Hull; Demetra Demetriou; David Owen Bates; Andreas Martin Kaufmann; Zodwa Dlamini; Rahaba Marima (Microorganisms, 2022)
Cervical cancer (CC) is the primary cause of female cancer fatalities in low-middle-income countries (LMICs). Persistent infections from the human papillomavirus (HPV) can result in cervical cancer. However, numerous different factors influence the development and progression of cervical cancer. Transcriptomic knowledge of the mechanisms with which HPV causes cervical cancer pathogenesis is growing. Nonetheless, there is an existing gap hindering the development of therapeutic approaches and the improvement of patient outcomes. Alternative splicing allows for the production of numerous RNA transcripts and protein isoforms from a single gene, increasing the transcriptome and protein diversity in eukaryotes. Cancer cells exhibit astounding transcriptome modifications by expressing cancer-specific splicing isoforms. High-risk HPV uses cellular alternative splicing events to produce viral and host splice variants and proteins that drive cancer progression or contribute to distinct cancer hallmarks. Understanding how viruses utilize alternative splicing to drive pathogenesis and tumorigenesis is essential. Although research into the role of miRNAs in tumorigenesis is advancing, the function of other non-coding RNAs, including lncRNA and circRNA, has been understudied. Through their interaction with mRNA, non-coding RNAs form a network of competing endogenous RNAs (ceRNAs), which regulate gene expression and promote cervical cancer development and advancement. The dysregulated expression of non-coding RNAs is an understudied and tangled process that promotes cervical cancer development. This review will present the role of aberrant alternative splicing and immunosuppression events in HPV-mediated cervical tumorigenesis, and ceRNA network regulation in cervical cancer pathogenesis will also be discussed. Furthermore, the therapeutic potential of splicing disruptor drugs in cervical cancer will be deliberated.